Why Clean Cooking Programs Fail Among Rural Women? A Female User-Centered View from Uttar Pradesh, India (Proceedings of the World Conference on Women’s Studies, 2021)
Many clean cooking programs around the world have invested in women to lead in the transition to cleaner cookstoves. However, in rural India, the lack of uptake from women is a major problem that has undermined the success of programs which expect women to act as champions of clean cookstoves in their community. To inform the theory of change of women-centered clean cooking programs and support future policymaking and programming in this field, this paper aims to address the knowledge gap on consumers’ – and especially women’s - attitude, knowledge and choice behavior towards improved cookstoves. In this paper, I use data from the ACCESS survey, collected in 2015 in Uttar Pradesh, to generate further gender-disaggregated evidence on the roles played by health impact awareness, intra-household power dynamics and access to finance on rural women’s behavior towards improved biomass cookstoves (IBCS). I identify the two most important shapers of women’s choice behavior towards IBCS as 1) level of satisfaction with traditional biomass cookstoves and 2) previous awareness and experience of IBCS. I find that Uttar Pradesh women are at once more unsatisfied with traditional unimproved biomass cooking practice, and more aware of IBCS technology. Whereas the former has a significant and positive effect in driving women towards adoption of IBCS, I find the latter in fact not only fails to mobilize demand but also undermines willingness to pay by about 40% on average. Through gender-lens market research in the improved biomass cookstoves market, this paper builds upon the evidence base for the design of more successful women-focused clean cooking programs.
Keywords: clean cooking; women’s health; rural environmental health; women’s consumption behavior; clean technology adoption